Kidnapped - Stevenson, Robert Louis. 1850-1894. (Toronto ; New York : Bantam, 1982)
The story of young David Balfour, and orphan, whose miserly uncle cheats him out of his inheritance and schemes to have him kidnapped, shanghaied, and sold into slavery.
Originally published: 1913.
Bibliography : p. 222-224.
13
Keywords: Adventure and adventurers -- Fiction; Scotland -- Fiction